Glycemic variability is higher in type 1 diabetes patients with microvascular complications irrespective of glycemic control - Šoupal, Jan; Škrha, Jan; Fajmon, Martin; Horová, Eva; Mráz, Miloš; Škrha, Jan; Prázný, Martin (Diabetes technology & therapeutics, 2014)
BACKGROUND: Increased glycemic variability (GV) may be associated with diabetes complications. Our study assessed the relationship between microvascular complications (MVCs) and GV calculated from continuous glucose monitoring (CGM) data in type 1 diabetes patients. SUBJECTS AND METHODS: Thirty-two patients with type 1 diabetes (16 with and 16 without MVC) participated in this cross-sectional study. Vibration perception threshold (VPT), microalbuminuria, and fundoscopy were used to detect MVC. CGM data were recorded for 2 weeks and analyzed using proprietary software. Total SD (SDT), coefficient of variation (CV), and mean amplitude of glycemic excursions (MAGE) were compared. RESULTS: Patients with any MVC had significantly higher GV, calculated from CGM, than patients without MVC (SDT, 4.1 ± 0.6 vs. 3.4 ± 0.8 mmol/L [P = 0.010]; CV, 0.43 ± 0.06 vs. 0.38 ± 0.08 [P = 0.032]; MAGE, 6.9 ± 1.2 vs. 5.9 ± 1.2 mmol/L [P = 0.014]) but comparable glycated hemoglobin (HbA1c) (70 ± 9 vs. 69 ± 10 mmol/mol [8.6 ± 0.8% vs. 8.5 ± 0.9%], difference not significant). No significant difference in GV was found between the two groups when using only self-monitored blood glucose (SMBG) data. A positive association was found between VPT and SDT in all patients (r = 0.51, P = 0.0026). CONCLUSIONS: Patients with type 1 diabetes and any MVC had significantly higher GV calculated from CGM, but not from SMBG, than patients with comparable glycemic control but without complications. This supports the hypothesis that increased GV might be associated with MVC in type 1 diabetes and that HbA1c may not describe diabetes control completely.
Keywords: Humans; lidé středního věku; Predictive Value of Tests; Blood Glucose Self-Monitoring; Female; analýza rozptylu; dospělí; Analysis of Variance; Albuminuria; Monitoring, Ambulatory; Diabetic Angiopathies; lidé; Biomarkers; Blood Glucose; selfmonitoring glykemie; diabetické angiopatie; vibrace; Glycated Hemoglobin A; albuminurie; diabetes mellitus 1. typu; Adult; biologické markery; ženské pohlaví; Male; Middle Aged; prediktivní hodnota testů; krevní glukóza; ambulantní monitorování; Vibration; Odds Ratio; Cross-Sectional Studies; průřezové studie; Risk Assessment; mužské pohlaví; odds ratio; glykovaný hemoglobin; hodnocení rizik; Diabetes Mellitus, Type 1; Glycated Hemoglobin